Perancangan Promotion Mix pada PT. Rambun Pratama Metalindo - Golan Hasan; Kelly Kelly (ConCEPt - Conference on Community Engagement Project, 2021)
In general, business owners have not seen how to formulate a strategy in marketing that is appropriate and can be implemented in developing business so that this business cannot develop properly. This practical work activity is carried out in one of the building shops in the city of Batam, namely: PT. Rambun Pratama Metalindo which was held in the period 21 September 2020 - 21 December 2020, activities for a period of 3 months carried out to help develop and solutions experienced by partners by implementing and designing the Marketing Mix Strategy. Development planning is described in several implementations that will be carried out, collaborating with third parties in crediting, providing discounts on purchases with specified transaction drinks, collaborating with contractors in supplying building material needs, making product catalogs, and creating customer databases.